2018
DOI: 10.1089/acm.2016.0346
|View full text |Cite
|
Sign up to set email alerts
|

Does Music Therapy Improve Anxiety and Depression in Alzheimer's Patients?

Abstract: A short protocol of music therapy can be an alternative medicine to improve emotional variables in Alzheimer patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
32
0
4

Year Published

2019
2019
2025
2025

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 66 publications
(39 citation statements)
references
References 8 publications
3
32
0
4
Order By: Relevance
“…The study showed that after music therapy, patients' cortisol levels decreased, which is relevant considering recent research which has shown that cortisol is significantly associated with increasing levels of depression (Keller et al, 2017). Not only did the research of Ortí et al (2018) solidify the previous research on cortisol and its effect on patients' depression, but it specifically showed that those suffering from depression within the context of another comorbid (co-occurring) disorder can still be treated with music therapy.…”
Section: Depression and Anxietysupporting
confidence: 53%
See 1 more Smart Citation
“…The study showed that after music therapy, patients' cortisol levels decreased, which is relevant considering recent research which has shown that cortisol is significantly associated with increasing levels of depression (Keller et al, 2017). Not only did the research of Ortí et al (2018) solidify the previous research on cortisol and its effect on patients' depression, but it specifically showed that those suffering from depression within the context of another comorbid (co-occurring) disorder can still be treated with music therapy.…”
Section: Depression and Anxietysupporting
confidence: 53%
“…For these patients, the song on flowers functioned to improve base cognitive levels, memory, and lyric recall, while also strengthening the temporal link between flowers and positive emotions associated with the season of spring. (Ortí et al, 2018).…”
Section: Depression and Anxietymentioning
confidence: 99%
“…Two studies with daily functioning as an outcome reported no significant improvements in the music therapy group [26,27]. Music therapy modalities in these trials included singing, playing musical instruments, and lyric reading.…”
Section: Daily Functioningmentioning
confidence: 99%
“…In contrast, passive MT interventions involve patients listening to music, rather than actively participating with or producing it. Distinctions between these two types of MT interventions are often not made clear in the literature (Bringas et al, 2015;Doro, Neto, Cunha, & Doro, 2017;de la Rubia Orti et al, 2017). Some research has stressed a distinction between the two (Atiwannapat, Thaipisuttikul, Poopityastaporn, & Katekaew, 2016;Erkkila et al, 2011); yet, differences between active and passive interventions vary and comparative studies that isolate specific components of musical engagement have yet to be conducted.…”
Section: Introductionmentioning
confidence: 99%